Prevalence, antecedents, and consequences of workplace bullying among employees in selected multinational corporations in Malaysia - S T Samanthar, Santhosh Kumari (2019)
For four decades, research reported workplace bullying as a widespread and harmful stressor, increasing interest among researchers globally in investigating its contributing factors, particularly organizational factors, which are still lacking in Malaysia. Therefore, this study explicitly aimed (1) to investigate the prevalence of workplace bullying (2) to describe the levels of organizational antecedents, namely, negative organizational culture, role ambiguity, role conflict, and destructive leadership and consequences of WB, namely, intention to leave and team cohesiveness, respectively, (3) to determine the relationship between organizational antecedents and workplace bullying (4) to determine the most dominant organizational antecedents influencing workplace bullying and finally (5) to determine the consequences of workplace bullying on the intention to leave and team cohesiveness in at Multinational Corporations Human Resource Shared Service Centres (MNC HRSSC) in Malaysia. The study has expanded the existing workplace bullying research by combining two conceptual frameworks (integrated model) through the structural relationship analysis between the study variables, confirming that organizational factors could lead to severe work and person-related bullying impacting employees’ eventually affecting the MNC HRSSC in the long run. General Strain Theory (Agnew, 1992) and Affective Event Theory (Weiss & Cropanzano, 1996) support and explain the relationships between the study variables. The present study employed a quantitative research method, specifically a cross-sectional design comprising descriptive and inferential analysis: the former used SPSS, and the latter employed Structural Equation Modeling (SEM). Through cluster sampling, data were collected using a self-administered questionnaire from 460 employees below the Senior Managerial level in MNC HRSSCs. The findings reported a high prevalence of workplace bullying. All the proposed organizational antecedents have a positive and significant relationship with workplace bullying, where role conflict is the dominant antecedent influencing the phenomenon. Workplace bullying also has a positive and significant relationship with the intention to leave and a negative relationship with team cohesiveness. Therefore, this study confirms the integrated model of workplace bullying in the context of MNC HRSSC. This study suggests that Human Resource Development professionals and policymakers make efforts and measures to create a positive work environment by creating awareness of workplace bullying, formulating strategies, stringent anti-bullying policies, leadership training, and counselling sessions for victims. Finally, the findings suggest the importance of having workplace bullying laws in Malaysia to protect and provide a safe, unthreatened work environment, assuring employee’s well-being, in line with the Global Plan of Action (2015-2025), proposed by the World Health Organization (WHO), which aims to shield and promote health in the workplace through prevention and control of psychosocial risks. The present findings propose further research on workplace bullying by expanding the research scope to other MNC Shared Service Centres to allow broader generalizations. Besides, future research should include other organizational antecedents to provide a comprehensive empirical-based explanation to strengthen the knowledge on workplace bullying and assist organizations in developing strategies to curtail workplace bullying in MNC Shared Service Centres. The present study used the Negative Acts Questionnaire-Revised version to measure workplace bullying, which was developed and deemed appropriate for Western culture. Hence, it is proposed that a more specific Malaysian context bullying questionnaire be developed, considering local context and culture.